Current Trends and Topics in U.S Citizenship, Law-Related and Economic Education - Grammes, Tilman (JSSE - Journal of Social Science Education, 2011)
The National Council of the Social Studies (NCSS) serves as one of the world’s largest professional communities. The 90th annual congress 2010 took place at Mile High City in Denver/Colorado. What is going on in U.S. civics, law-related and economics education? The following congress report presents an overview on educational policy, research and curriculum projects, to facilitate the reader outside the U.S. a quick information about the state-of-the-art.